The grand food bargain : and the mindless drive for more - Walker, Kevin D., 1955- (Island Press, 2019)
Americans enjoy some of the cheapest, most convenient food on the planet. But like most bargains that are too good to be true, the modern food system is a fraud. It is built on the illusion of limitless abundance, and the planet has its limits. So too do the workers who must labor harder and faster for less pay. So too does a healthcare system that must absorb rising rates of diabetes and obesity. Through stories from around the globe, Kevin Walker reveals the true costs of our grand food bargain. By the end of the journey, we not only understand how the drive to produce ever more food became hardwired into the American psyche, but why shifting our mindset is essential.